Land-use and climate related drivers of change in the reindeer management system in Finland : Geography of perceptions - Rasmus, Sirpa; Wallen, Henri; Turunen, Minna; Landauer, Mia; Tahkola, Juho; Jokinen, Mikko; Laaksonen, Sauli (Applied Geography, 2021)
Drivers of change in the reindeer management system are rather well-known. But when developing the gover-nance to support the traditional livelihoods, it is crucial to understand also practitioner perceptions. Systematic research on these is lacking. We analyzed the land-use and climate related drivers within the reindeer man-agement area (RMA) in Finland, and, using a perception geography approach, studied the herder perceptions towards these. We conducted an on-site questionnaire survey with herders from 51 herding districts. Factors directly affecting the welfare of reindeer were perceived as crucial by herders, for example basal icing affecting the forage availability, and land-use related factors limiting the seasonal pasture access. Perceptions of herders on biophysical factors were rather homogeneous. The regional heterogeneities in perceptions towards land-use related factors could be explained by spatial differences in land-use and varying herding traditions. Cumulative land-use impacts raised particular concerns. Our approach can be utilized in the co-planning of the northern land-use and more widely in the co-management of natural resources. Peer reviewed